Innovation in Authentic Assessment of Receptive Skills in the Arabic Language Textbook for Grade IV, Ministry of Religious Affairs 2020 - Saariah; R. Umi Baroroh; Rita Diana; Syarah Yunita; Ainun Mawaddah (Hasanuddin University, 2024)
This study investigates the evaluation of receptive skills within a textbook using an authentic assessment approach. The focus is on the reading skills component of the Arabic language textbook for Grade IV of Islamic Elementary Schools (MI), published by the Ministry of Religious Affairs in 2020. Employing a qualitative descriptive methodology with a critical analysis framework, the research utilizes observation and documentation as data collection methods. Findings suggest that the assessment of receptive language skills primarily falls under the knowledge domain. Authentic assessment of these skills can be achieved through various methods such as projects, interviews, or assignments. Examples include summarizing orally presented texts, creating visual representations based on auditory descriptions, engaging in conversations that reflect the content heard, or composing texts that are analogous to the auditory input received. Keywords: Innovation Assessment; Receptive Skills; Authentic Assessment.